EVENT BASED MARKETING STUDI KASUS TELEMARKETING BANCASSURANCE CARD BUSINESS PAD A PT BANK DANAMON INDONESIA - , Meita Indriasari; , Dr. lin Maya Sari, M.M., MSi. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Bancassurance is the cooperation between bank and insurance company to sell insurance product to Bankâs customers. Bancassurance products can be sold by sales forces in the Bankâs branches or through Telemarketing. Bank Danamon has cooperation with AIA Insurance, ACE Insurance, Cigna Insurance, Chartis Insurance, and Manulife Insurance in doing bancassurance telemarketing. Bancassurance telemarketing activities are done for Consumer Banking customers in Retail Banking and Unsecured Personal Loan, Small Medium Ecterprise customers, and Card Business customers. Offer to Unsecured Personal Loan and Small Medium Enterprise just started in January 2013 as one of marketing expansion initiatives. Until end of 2012, Danamon bancassurance telemarketing activities only done for saving account owners in Retail Banking and card holder in Card Business. Bancassurance telemarketing in Retail Banking has shown a good result eventhough developments still needed. In the contrary, bancassurance telemarketing in Card Business show a low and below target productivity. Few initiatives has been taken to improve productivity of card business bancassurance telemarketing since early 2012, include applying scoring system for database screening and doing telemarketing activities in three different call center, which are Danamon Call Center, Manulife Call Center, and Third Party Call Center. After three months competition, Manulife Call Center were selected to do Card Business bancassurance telemarketing activities. However, the productivity still far below target. Manulife Insurance planned to improve Card Business bancassurance telemarketing by event based marketing trial implementation on Card Business customer database. If the trial succeded, it would be possible to implement event based marketing on other segment in Bank Danamon.